Herramienta SIG para el inventario de Arte Rupestre en los municipios de Bojacá, Soacha, Sutatausa y Tenjo de Cundinamarca (2023)
This work is based on the inventory information of sites with Rock Art in the municipalities of Bojacá, Soacha, Sutatausa and Tenjo in the department of Cundinamarca carried out through programs of the respective municipalities and the Erigaie Foundation through the Rock Art manager Diego Martínez Celis. A control board of archaeological heritage specialized in Rock Art was created where the user interacts with the information of the different stones in the municipalities of Bojacá, Soacha, Sutatausa and Tenjo. In it you can know the list and quantity of stones of the municipality, details of the rock as descriptions, owner, accessibility and observations. This GIS tool contributes to the knowledge and appropriation of cultural heritage.